New Topology LNA Architecture using Inductive Drain Feedback Technique for Wireless Application - Kamil bin Pongot; Othman A.R; Zakaria Z; Suaidi M.K; Hamidon A.H (Institute of Advanced Engineering and Science, 2014)
This paper presents a design of a single LNA cascaded with double stage cascoded LNA amplifiers using an inductive drain feedback technique. The amplifier it is implemented using superHEMT FHX76LP transistor devices. The designed circuit is simulated with Ansoft Designer SV. The LNA was designed using inductive drain feedback, inductive generation to the source, and the T-network as a matching technique was used at the input and output terminal. The low noise amplifier (LNA) provides a gain (S21) of 68.94 dB and the noise figure (NF) of 0.64 dB. The return loss (S12) output reflection (S22) and input reflection (S11) are -88.39,-17.37 and –15.77 dB respectively. The measurement shows a 3-dB bandwidth of 1.72 GHz and stability are 4.54 more than 1 has been achieved. The input sensitivity is -92 dBm exceeded the standards required by IEEE 802.16.